Revision of the Neotropical vallensis species-group (Hymenoptera, Bethylidae, Dissomphalus), with the discovery of fifteen new species - Pereira, Leonardo R.; Brito, Chirlei D. De; Azevedo, Celso O. (Zootaxa, 2026)
Dissomphalus Ashmead is the most speciose Bethylidae genus, with the majority of its species found in the Neotropical region. Due to this high diversity, the species are organized into species-groups, mainly based on metasomal tergal processes and the male genitalia. The vallensis species-group is defined by having two tubercles mesad located in a median subcircular or elliptical fovea, tufts of setae are common in the lateral region inside this depression. Currently, this group comprises 20 valid species. Here, we revise this group and describe fifteen new species: D. angroni sp. nov., D. corvusi sp. nov., D. eliasi sp. nov., D. firminoi sp. nov., D. fulgrimi sp. nov., D. horusi sp. nov., D. jaghataii sp. nov., D. lorgari sp. nov., D. magnusi sp. nov., D. mortarioni sp. nov., D. perturaboi sp. nov., D. roboutei sp. nov., D. rogali sp. nov., D. sanguiniusi sp. nov., and D. vulkani sp. nov. The male genitalia characters play a critical role for species delimitation, with others characters having a limited taxonomic value. We also provide a new identification key for all males and new information about their distribution, with most of them found in Brazil with D. bifurcatus having the largest distribution along the Neotropical region. The genus includes 639 valid species globally with this contribution.